2023
DOI: 10.3389/fnins.2023.1131247
|View full text |Cite
|
Sign up to set email alerts
|

Altered dynamic functional connectivity in the primary visual cortex in patients with primary angle-closure glaucoma

Abstract: PurposeGlaucoma is the main blindness-causing disease in the world. Previous neuroimaging studies demonstrated that glaucoma not only causes the loss of optic ganglion cells but also leads to the abnormal function of the optic nerve pathway and the visual cortex. However, previous studies also reported that patients with glaucoma have dysfunction in the visual cortex in a static state. Whether or not patients with primary angle-closure glaucoma (PACG) were accompanied by dynamic functional connectivity (FC) ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
(29 reference statements)
1
2
0
Order By: Relevance
“…Our study found enhanced functional connectivity in the visual network of PACG patients, consistent with the results of Li et al (51). However, Dai et…”
Section: Discussionsupporting
confidence: 93%
“…Our study found enhanced functional connectivity in the visual network of PACG patients, consistent with the results of Li et al (51). However, Dai et…”
Section: Discussionsupporting
confidence: 93%
“…Some scholars have utilized rs-fMRI to determine whether amblyopic patients have functional changes in the brain areas along this pathway, i.e., from the cerebellum, inferior parietal lobule to V1 [27][28][29][30][31][32] . A similar study found that the functional connection between the right anterior cerebellar lobe and primary visual cortex is decreased in patients with glaucoma-associated optic nerve damage, and even the higher visual cortex has similar manifestations, suggesting that there is a decline in visual integration in these patients [33] . It is suggested that the decrease in the function of the anterior cerebellar lobe may be caused by the decrease in information input in the primary or higher visual cortex.…”
Section: Discussionmentioning
confidence: 68%
“…Structurally, patients with glaucoma exhibit white matter tract damage far beyond visual pathway localization 34 . Functionally, PACG patients show visual dysfunction and vision-related cortex dysfunction 35 , 36 . These studies suggest that PACG patients have abnormalities in their visual networks, both structurally and functionally.…”
Section: Discussionmentioning
confidence: 99%